Effect of added Ni on defect structure and proton transport properties of indium-doped barium zirconate. (24th January 2020) - Kuroha, Tomohiro; Yamauchi, Kosuke; Mikami, Yuichi; Tsuji, Yoichiro; Niina, Yoshiki; Shudo, Mizuki; Sakai, Go; Matsunaga, Naoki; Okuyama, Yuji
Abstract: We investigated the influence of Ni on protonic ceramic fuel cells based on indium-doped barium zirconate. A tubular fuel cell was fabricated and evaluated with BaZr0.8 In0.2 O3−δ as an electrolyte. The maximum power density was 0.143 W cm −2 and the ohmic resistance of the electrolyte was 0.91 Ω cm 2 at 873 K. We used secondary ion mass spectrometry to measure the dissolution of Ni in the electrolyte N to be 0.015. To clarify the effect of Ni on proton transport properties of BaZr0.8 In0.2 O3−δ, electrical conductivity and proton concentration were measured by AC impedance analysis and thermogravimetric analysis. Electrical conductivity decreased as the NiO content increased. Conversely, proton concentration was independent of the NiO content and proton diffusivity decreased. The sample density also depended on the NiO content. The density decreased as NiO content increased. These results were consistent with the density calculated based on a model describing formation of oxygen vacancies. Highlights: A tubular cell is fabricated with the use of BaZr0.8 In0.2 O3−δ . The average dissolution of Ni in the electrolyte N is measured by SIMS to be 0.015. The electrical conductivity decreases as the NiO content increases. The density decreases as the NiO content increases.